2017
DOI: 10.3892/ol.2017.7109
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the associations between human circadian rhythms and dysregulated genes in liver cancer cells

Abstract: Network analysis is a useful approach in cancer biology as it provides information regarding the genes and proteins. In our previous study, a network analysis was performed on dysregulated genes in HepG2 cells, a hepatoblastoma cell line that lacks the viral infection, compared with normal hepatocytes, identifying the presence of 26 HUB genes. The present study aimed to identify whether these previously identified HUB genes participate in the network that controls the human circadian rhythms. The results of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 66 publications
2
7
0
Order By: Relevance
“…Research by the International Agency for Research on Cancer has also demonstrated that this disruption increases the risk of CRC (7). Several previous studies have also demonstrated that large variations in expression levels, both up- and downregulated, and the circadian clock genes are associated with tumor progression and mammalian tumorigenesis for several malignancies, such as breast cancer (8), liver cancer (9) and colorectal carcinoma (10). In addition, the association between single nucleotide polymorphisms (SNPs) in circadian clock genes and disease has also been analyzed (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Research by the International Agency for Research on Cancer has also demonstrated that this disruption increases the risk of CRC (7). Several previous studies have also demonstrated that large variations in expression levels, both up- and downregulated, and the circadian clock genes are associated with tumor progression and mammalian tumorigenesis for several malignancies, such as breast cancer (8), liver cancer (9) and colorectal carcinoma (10). In addition, the association between single nucleotide polymorphisms (SNPs) in circadian clock genes and disease has also been analyzed (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…A large quantity of studies have suggested that circadian disruptions are closely associated with the formation and development of various diseases including cancer (Momma et al, 2017; Polo et al, 2017; Xiong et al, 2018), dysplasia (Vilches et al, 2014; Voiculescu et al, 2016; Zhao et al, 2018; Zhou et al, 2018), cardiovascular disease (Angelousi et al, 2018), obesity (Antunes et al, 2010), diabetes (Pan et al, 2011), and sleep disorder (Logan and McClung, 2019). As previously described, the cell cycle and the circadian clock are two basic periodic processes of a day, and they are interrelated.…”
Section: Circadian Rhythm Disorder and Diseasesmentioning
confidence: 99%
“…Simultaneously, CKAP5 was associated with three circadianrelated genes (CSNK1E, CSNK1D, and HDAC4). Furthermore, it was found that miR-195-5p, miR-192-5p, miR-122-5p, and miR-101-3p were involved in the dysregulation of circadian genes which led to HCC [76]. A series of miR-NAs targeting circadian genes have been identified using ENCORI (http://starbase.sysu.edu.cn/) [77].…”
Section: The Posttranscriptional Regulation Of Circadian Genes Bymentioning
confidence: 99%